La estimulación de la conciencia fonológica y su influencia en el aprendizaje inicial de la lectoescritura en niños y niñas de primer año de educación básica de la escuela Miguel Riofrío de la ciudad de Loja, periodo 2014 - Japon Gonzalez, Jhuly Maria (2015)
This research was: Stimulation phonological awareness and its influence on the initial learning literacy in children first year basic education school Miguel Riofrío of the Loja city, period 2014. For this a general object to state with the intention to make a scientific study that allowed to have a knowledge development phonological of the children in literacy learning initial. In this research: the methods were used as a: Descriptive scientific, statistical, inductive-deductive. Technique used psicopedagogic survey was structured 7 questions for all 4 teachers for measuring the other variable is use assessment test awareness phonological applied to children in order to get the results were interpreted and discussed. Population of children was 94 and teachers were 4 and 28 children of the first year basic education school Miguel Riofrío. The results was than the level of awareness development in children phonological of the first year basic education 9 children is equivalent to 32% present to a high level of awareness development phonological; 8 children is equivalent to 29% presented an intermediate level or a normal level in developing awareness phonological ; 11 children is equivalent to a 39% presented developing low level of awareness so phonological concludes that there is a high index of children who have not developed the phonological awareness. Concludes that were there are differences in the development of consciousness among children phonological; girls got a 78% and children got a 55% on the evaluation of conscience phonological. There is a high index of children who have not developed the phonological awareness to have a knowledge development phonological of the children in literacy learning initial. Concludes that is global using methods and teaching phonetic have direct relationship with awareness development in children phonological; 2 teachers are equivalent to a 50% phonetic apply method; 2 teachers are equivalent to 50% global method applying.